Arredor do Rexurdimento. Apuntamentos xerais. - MARTÍNEZ GONZÁLEZ, XURXO (Scripta, 2020)
This is a study of the current state of the Rexurdimento´s research. Based on an updated bibliography, we analyze de galician renaissance and make our contribution in terms of definition, chronology, central characteristics, contribution to the national colectiva imaginary and the valeu of language as ca entral element in the constrution of identity and philological criteria in literatura. The study is based on the relationship between the political and cultura fields. We take, mainly, the Xoán González-Millán, Antón Figueroa and Alejandro Alonso Nogueira´s studies.